Multilayer sheets for thermoforming non thermoformable polymers - Wittmann, Lisa-Maria; Drummer, Dietmar (Journal of Plastic Film & Sheeting, 2021)
Multilayer sheets were used for thermoforming non thermoformable polymers in order to face the challenge of semi-crystalline polymers like low melt-stiffness. Mono- and 2-layer sheets consisting of different polypropylene (PP) homopolymers were extruded on a twin screw extruder. The PP viscosity as was measured by melt flow rate (MFR) 3 g/10 min., 12 g/10 min., 22 g/10 min. and 50 g/10 min. The layer ratio was varied between the equal layer ratio (A50/B50) of the individual layers and the low (A30/B70) or high viscosity ratio (A70/B30). The extrusion results show that for extreme viscosity differences (MFR3 and MFR50), the critical layer ratios known from the literature are only valid to a limited extent. The critical viscosity ratio < 4, which is known from the literature, is much lower here and should be less than 3. The investigation of thermoformability on laboratory scale of the extruded PP sheets with different viscosities showed that the low viscous layer position has only a marginal influence on the general thermoformability. Thermoforming of materials that are not thermoformable, with a storage modulus of less than 10³ Pa and a ratio between storage and loss modulus (tan δ) greater than 1, becomes possible using a multilayer sheet independant of the layer ratio. If the layer with higher viscosity acts as a stabilizing layer, thermoforming is possible.
CRIS-Team Scopus Importer:2021-08-13
Keywords: multilayer; strain developement; Thermoformability; viscosity; wall thickness